Comparison of the clinical performance between two types of implant abutment - سليمان زين العابدين; ريمة صقر (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: The material composition of the abutment is a factor affecting the stability of the soft and hard tissues surrounding the dental implant and has a role in reducing marginal bone resorption and soft tissue reaction. Titanium (Ti) abutment were mainly used over dental implants, but abutments made of stainless steel (SS) and foldable have now been introduced to suit critical cases in placing implants within the bone and to reduce procedures, costs, time and effort for the patient, doctor and laboratory, but the reaction of soft and hard tissues towards it is a matter of controversy. Purpose: Evaluate the clinical performance of Ti abutments and SS abutments. Materials and Methods: sixteen dental implants (Arcsys-FGM) that were placed symmetrically in the upper premolar area. It was divided into two groups equally: the first received titanium abutment and the second received foldable stainless steel abutment and final zirconia restorations were used. Radiological monitoring was conducted 3-6-12 months after loading using the angulation technique to study the marginal bone lose, and the probing depth (PD) and bleeding index (BI) were measured during the observation period. Results: there were no statistically significant differences in the average marginal bone loss between the implants that received Ti abutment and the implants that received foldable SS abutment, as it reached (0.46) mm in the first and (0.39) mm in the second. It was noted that there were no statistically significant differences in PD and BI between the two groups. Conclusion: foldable SS abutment is clinically acceptable in terms of marginal bone loss and biological complications compared to the Ti abutment.